Occurrence of Escherichia coli in meat preparations - Robina, Ana (Array, 2018)
Meat preparations are produced from one or more types of minced meat with added seasonings or additives, and are usually placed on the market under labels: ćevapčići, meat patty or hamburger/burger. The bacterial contamination of such products with Escherichia coli during production and distribution is invariably possible. In this paper, we have tested 50 samples of meat preparations for bacteria E. coli, whose presence points to the faecal contamination of food. Only 8 % of meat preparation samples had an E. coli count of less than 500 cfu/g, suggesting that all samples tested in this study yielded satisfactory results regarding the prescribed microbiological criteria for food.